2012
DOI: 10.2108/zsj.29.538
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Diversity of the Eel Goby, GenusTaenioides(Gobiidae: Amblyopinae), in Japan

Abstract: The eel goby, genus Taenioides (Gobiidae: Amblyopinae), inhabits muddy bottoms of estuaries or shallow areas of seas in the Indo-Pacific Ocean. Among congeners, T. cirratus ( Blyth, 1860 ) has been thought to be distributed in Japan, but taxonomic confusions remain as to which scientific names are applicable to Japanese Taenioides species, or more fundamentally, how many Taenioides species are distributed in Japan, due in part to the rarity of this group in museum collections and the morphological similarity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 16 publications
5
16
1
Order By: Relevance
“…kentalleni Murdy & Randall 2002, but they recognized that their identifications required verification with examinations of the type specimens. Murdy (2018) agreed with Kurita and Yoshino (2012) after examination of the type specimens of the four species. Three of the four species, T. anguillaris , T. gracilis and T. kentalleni , are distributed on Okinawa Island (Kurita & Yoshino, 2012).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…kentalleni Murdy & Randall 2002, but they recognized that their identifications required verification with examinations of the type specimens. Murdy (2018) agreed with Kurita and Yoshino (2012) after examination of the type specimens of the four species. Three of the four species, T. anguillaris , T. gracilis and T. kentalleni , are distributed on Okinawa Island (Kurita & Yoshino, 2012).…”
Section: Resultssupporting
confidence: 77%
“…We examined three larval specimens and found that their dorsal‐, anal‐ and pectoral‐fin‐ray counts are within the ranges of those established for T. snyderi and T. gracilis in Koreeda and Motomura (2021), Kurita and Yoshino (2012), and Miyahira and Tachihara (2022) (Tables 6–8). The dorsal‐ and anal‐fin‐ray counts are almost the same as those established for the paralectotype of T. snyderi and holotype of T. gracilis (total dorsal‐fin elements, 53–54 in larvae vs .…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…As Leucopsarion petersii only appears in tidal rivers during spawning season and Acanthogobius hasta only appears during the juvenile period, these species were also excluded from the analysis. Although there are four Taenioides species in Japan (Kurita & Yoshino, 2012; Murdy, 2018), these are taxonomically confused with each other. Therefore, they were treated as one species, Taenioides cirratus , in accordance with the Ministry of the Environment (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Although the identifications of four species need additional verifications, they were identified as T. anguillaris, T. snyderi, T. gracilis and T. cf. kentalleni, and the species name T. cirratusdoes not seem to be appropriate to any of four detected species (Kurita and Yoshino 2012).…”
Section: Introductionmentioning
confidence: 93%